The Role Of Digital HR In Improving Indonesian Human Resource Competence In The Era Of Industry 4.0 Transformation - Azuwandri Azuwandri (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
The transformation of Industry 4.0 has fundamentally changed the way organizations manage human resources, requiring employees to possess higher levels of digital and adaptive competencies. In Indonesia, many organizations still face challenges in preparing a workforce that is able to respond to rapid technological disruption. This study aims to analyze the role of Digital Human Resources (Digital HR) in improving Indonesian human resource competence in the era of Industry 4.0 transformation.This research applies a quantitative approach with an explanatory design. Data were collected through questionnaires distributed to employees and HR practitioners in organizations that have implemented Digital HR practices. The variables examined include digital recruitment, digital learning and development, digital performance management, and HR analytics as dimensions of Digital HR, while human resource competence is measured through technical, digital, and behavioral competencies. The data were analyzed using multiple regression/SEM to examine the influence of Digital HR on HR competence.The results indicate that Digital HR has a positive and significant effect on the improvement of human resource competence. Among the dimensions, digital learning shows the strongest contribution, followed by HR analytics and digital recruitment. The findings highlight that technology-based HR management plays a strategic role in developing competitive Indonesian human resources. This study provides practical implications for organizations to strengthen Digital HR implementation in order to support sustainable competency development in the Industry 4.0 era.